Advances in MOF-enabled food preservation and packaging: A critical review of structure-function relationships, functionalization strategies, applications, and safety - Yinghua Tang; Yuqin Feng; Xuefeng Liu; Kuiran Liu; Wenhua Mu; Yating Song; Yuqing Duan; Guishan Liu (Food Research International, 2026)

Electrospun nanofiber interfaces for aquatic products preservation: spoilage microenvironments, molecular interactions, and mechanism-oriented design strategies - Kuiran Liu; Yuqin Feng; Xuefeng Liu; Yinghua Tang; Wenhua Mu; Yating Song; Yuqing Duan; Guishan Liu (Food Bioscience, 2026)

Sustainable bio-aerogels for food packaging applications: Fabrication strategies, preservation mechanisms, and innovation trends - Xuefeng Liu; Yuqin Feng; Yating Song; Jiajun Guo; Kuiran Liu; Yinghua Tang; Wenhua Mu; Jianfang Li; Yuqing Duan; Guishan Liu (Food Research International, 2026)

New pterosins from Hypolepis punctata - Liang Shen; Wenhao Mu; Peixin Wang; Maoni Ren; Yating Jia; Xiaoran Min; Jiajia He; Guozheng Huang; Hui Shen; Jianguo Cao (Journal of Natural Medicines, 2025)

Coexisting plants restored in karst desertification areas cope with drought by changing water uptake patterns and improving water use efficiency - Lulu Cai; Kangning Xiong; Yuan Li; Ziqi Liu; Dayun Zhu; Hong Liang; Yating Mu; Yi Chen (Journal of Hydrology, 2025)

Nanocomposite hydrogel with multiple metal ions coupling for effective treatment of bacteria infected wound via cascade catalysis and tissue regeneration - Yating Liu; Wenyun Mu; Yu Wang; Tao Liu; Zhenzhen Peng; Xin Chen (Chemical Engineering Journal, 2025)

Water competition among coexisting plants in rock-dominated habitats of subtropical karst desertification - Lulu Cai; Kangning Xiong; Ziqi Liu; Yuan Li; Dayun Zhu; Yating Mu; Yi Chen; Rong Zhou; Xiaoyu Yan (Agriculture, Ecosystems & Environment, 2025)

Digital one-pot SHERLOCK assisted superfast and reverse transcription free method for circulating microRNA absolute quantification - Zheyu Zou; Juxin Yin; Liping Xia; Weihong Yin; Ke Liu; Yating Pan; Kai Hu; Yehong Gui; Jianjian Zhuang; Duo Xiao; Ying Mu (Chemical Engineering Journal, 2025)

Inclusion of Lonicerae flos improved anaerobic fermentation and antioxidant activity of mixed silage (agro-residue and alfalfa) - Lin Mu; Xin Cao; Yating Wang; Qinglan Wang; Zhifei Zhang (Animal Feed Science and Technology, 2024)

Response of soil organic carbon to land-use change after farmland abandonment in the karst desertification control - Yating Mu; Runcheng Ye; Kangning Xiong; Yue Li; Ziqi Liu; Yidong Long; Lulu Cai; Qingping Zhou (Plant and Soil, 2024)

UFBSM: unmixing fusion and background sparse dictionary Model for hyperspectral anomaly detection - Xianghai Wang; Yihan Wang; Zhenhua Mu; Yating Zhang (International Journal of Remote Sensing, 2024)

Trim and Engine Power Joint Optimization of a Ship Based on Minimum Energy Consumption over a Whole Voyage - Yanyun Yu; Hongshuo Zhang; Zongbao Mu; Yating Li; Yutong Sun; Jia Liu (Journal of Marine Science and Engineering, 2024)
Trim optimization is an available approach for the energy saving and emission reduction of a ship. As a ship sails on the water, the draft and trim undergo constant changes due to the consumption of fuel oil and other consumables. As a result, the selection of the initial trim is important if ballasting or shifting liquid among the tanks is not considered during a voyage. According to the characteristics of ship navigation and maneuvering, a practical trim optimization method is proposed to identify the Optimal Trim over a Whole Voyage (OTWV) which makes the fuel consumption of the voyage minimum. The calculations of speed vs. draft and trim surfaces are created according to hull resistance data generated by CFD, model tests, or real ship measurements, and these surfaces are used to calculate the OTWV. Ultimately, a trim and Main Engine (ME) power joint optimization method is developed based on the OTWV to make the total fuel consumption minimum for a voyage with a fixed length and travel time. A 307000 DWT VLCC is taken as an example to validate the practicality and effect of the two proposed optimization methods. The trim optimization example indicates that the OTWV could save up to 1.2% of the total fuel consumption compared to the Optimal Trim at Initial Draft (OTID). The trim and ME power joint optimization results show that the proposed method could steadily find the optimal trim and ME power combination, and the OTWV could save up to 1.0% fuel consumption compared to the OTID in this case.

Structural priming from simple arithmetic to Chinese ambiguous structures: evidence from eye movement - Tao Zeng; Yating Mu; Taoyan Zhu (Cognitive Processing, 2021)